Perception and Challenges Dataset on Listening and Speaking Skills among Final-Year University Students in Dhaka - Mohammad Golam, Mohiuddin; Mansur, Ahmed Al; Fatema, Tuz Johra; Farjana, Tasnim Fariha; Md. Shamim, Mondol; Serajum, Munira; Islam, Md Imamul; Sultana, Zinat; Zuraina, Ali
This dataset contains responses from 83 final-year students at a private university in Dhaka, collected via a detailed questionnaire. The survey covers three sections: background information, listening skills, and speaking skills, with a mix of close-ended and open-ended questions. The close-ended questions use a 5-point Likert scale to gauge students' perceptions of challenges and strategies for improvement. Additionally, qualitative data were gathered through in-depth interviews with three teachers from the same university. The dataset has been normalized and is valuable for understanding students' language skill challenges in an academic context.